2014
DOI: 10.1038/eye.2013.299
|View full text |Cite
|
Sign up to set email alerts
|

Blebitis with scleral abscess in a case of operated trabeculectomy with mitomycin C and a subcunjunctival ologen implant

Abstract: Sir, Blebitis with scleral abscess in a case of operated trabeculectomy with mitomycin C and a subcunjunctival ologen implantWe report a case of juvenile open-angle glaucoma who underwent mitomycin-augmented trabeculectomy with subconjunctival ologen implantation, and subsequently developed scleral abscess and endophthalmitis. Case reportA 19-year-old male presented with BCVA of 6/24 OD and 6/6 OS. His intraocular pressure was 20 mm Hg OD and 18 mm Hg OS on maximal medical therapy with a vertical cup:disc rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…CMI are used as an adjunct to trabeculectomy to prevent surgical site fibrosis. [123] Typically, the size of CMIs is around 6 × 2 mm in diameter, whereas dimension of the sclerostomy site is much less. [45] Hence, spontaneous migration of an intact implant is highly unlikely, though other complications, such as bleb leakage, conjunctival atrophy, implant exposure, and endophthalmitis are known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMI are used as an adjunct to trabeculectomy to prevent surgical site fibrosis. [123] Typically, the size of CMIs is around 6 × 2 mm in diameter, whereas dimension of the sclerostomy site is much less. [45] Hence, spontaneous migration of an intact implant is highly unlikely, though other complications, such as bleb leakage, conjunctival atrophy, implant exposure, and endophthalmitis are known.…”
Section: Discussionmentioning
confidence: 99%
“…[45] Hence, spontaneous migration of an intact implant is highly unlikely, though other complications, such as bleb leakage, conjunctival atrophy, implant exposure, and endophthalmitis are known. [23] As CMIs may act as a nidus of infection,[2] these eyes may be at a high risk of infection in the setting of an open globe injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dada et al reported a case of blebitis with scleral abscess in a young patient who had undergone a trabeculectomy with MMC and a subconjunctival Ologen implant. 28 Meticulous conjunctival closure should be done at the end of trabeculectomy as exposed collagen can act as a nidus of infection.…”
Section: Introductionmentioning
confidence: 99%